The Influence of Competitive Strategy on Export Performance Through Competitive Advantage with Firm Age Moderation in the Indonesian Export Channel (IEC) Community of MSMEs - Elsavira Nandya; Agus Maolana Hidayat; Anita Silvianita (International Journal of Applied Business and International Management, 2024)
The global market's increasing dynamism and competitiveness push businesses to expand beyond national borders, aiming to enhance domestic and international competitiveness. This study investigates the influence of competitive strategy on export performance through competitive advantage, moderated by firm age, within the Indonesian Export Channel (IEC) Community of MSMEs. Employing a quantitative descriptive approach, data were analyzed using the SMART PLS statistical method. The findings reveal that competitive strategy significantly enhances competitive advantage, which in turn positively impacts export performance. However, the direct effect of competitive strategy on export performance was found to be negative and insignificant, suggesting that competitive strategy alone is insufficient to drive export success. Firm age significantly moderates the relationship between competitive advantage and export performance, highlighting the importance of considering firm-specific characteristics in strategic planning. This research underscores the need for MSMEs to adopt innovative approaches tailored to market demands, aligning competitive strategies with their competitive advantages to overcome barriers and achieve sustainable growth in export markets.